The Economic Benefits of Taylor Swift’s Eras Tour - Zhang, Weihua (Transactions on Economics, Business and Management Research, 2024)
Taylor Swift's "Eras Tour" is the sixth world tour held in 2023. It plans to hold 151 events worldwide until the end of 2024. Eras Tours are attracting more and more attention from the government and citizens than before, however, their potential economic value has not been uncovered. This article will use Eras Tour as a case study to explore and analyze the multifaceted and far-reaching impact of concerts on economic growth and learn more about how the profitability of large-scale concerts will drive the overall economy, and how governments and planners can use this profitability to boost the city's economy and regional brand. In addition, the article will point out that large-scale concerts are an opportunity to promote the sustained growth of the city's economy by increasing consumer spending and promoting tourism, catering and other industries, and that cities and local governments should make better use of this opportunity to actively introduce celebrity performances to promote economic prosperity.